Developing quantitative instruments for research purposes and data collection process. (2013)
The development of instruments is an essential component of research because without these instruments, data inputs in the form of raw information that will be used to analyse the participants' responses, views/opinions and knowledge in the particular area of study will not be there. It is also important that a research has the knowlege base on available instruments that can be used for data collection, as well as the skills in the development of these instruments to ease the processes of analysis and interpretation. Instruments constructed must be used to collect data systematically to ensure reliability and validity of the information gathered. Otherwise, the researcher could make error of judgement while interpreting the results. In view of this, module 2 has been divided into three units viz: developing instruments in the cognitive domain, developing instruments in affective and psychomotor domains and data collection process.